Exercise intensity governs tumor control in mice with breast cancer - Gomes-Santos, Igor L.; Kumar, Ashwin S.; Hausmann, Franziska; Meyer, Max N.; Shiferaw, Sarah Z.; Amoozgar, Zohreh; Jain, Rakesh K.; Fukumura, Dai (Frontiers in Immunology, 2024)
Exercise is recommended as an adjunct therapy in cancer, but its effectiveness varies. Our hypothesis is that the benefit depends on the exercise intensity. We subjected mice to low intensity (Li), moderate intensity (Mi) or high intensity (Hi) exercise, or untrained control (Co) groups based on their individual maximal running capacity. We found that exercise intensity played a critical role in tumor control. Only Mi exercise delayed tumor growth and reduced tumor burden, whereas Li or Hi exercise failed to exert similar antitumor effects. While both Li and Mi exercise normalized the tumor vasculature, only Mi exercise increased tumor infiltrated CD8+ T cells, that also displayed enhanced effector function (higher proliferation and expression of CD69, INFg, GzmB). Moreover, exercise induced an intensity-dependent mobilization of CD8+ T cells into the bloodstream. These findings shed light on the intricate relationship between exercise intensity and cancer, with implications for personalized and optimal exercise prescriptions for tumor control.Exercise is a widely recommended adjunct therapy for patients with cancer, offering potential benefits to both physical and psychological well-being. However, the optimal parameters for prescribing exercise as a therapeutic intervention remain a subject of debate [1]. Among many variables that may be taken in consideration for aerobic exercise prescription, the intensity of exercise deserves close attention. Personalizing exercise intensity accounts for the intrinsic variations in individual aerobic capacity and ensures that interventions are tailored to an individual's relative metabolic demands. This concept, central to exercise physiology [2], holds particular significance in the context of cancer, where a refined approach to exercise prescription is needed. In preclinical models, we and other researchers have investigated the effects of exercise on the tumor microenvironment (TME) and tumor control [3][4][5][6][7][8]. Notably, our previous report revealed a pivotal role of moderate continuous aerobic exercise in promoting a CD8+ T cell-mediated